Are preterm birth and intra-uterine growth restriction more common in Western Australian children of immigrant backgrounds? A population based data linkage study - Ifrah Abdullahi; Kingsley Wong; Emma Glasson; Raewyn Mutch; Nicholas de Klerk; Jenny Downs; Sarah Cherian; Helen Leonard (BMC, 2019)
Abstract Background To compare the prevalence of preterm birth, post term birth, intra-uterine growth restriction and distribution of Apgar scores in offspring of foreign-born women in Western Australia with that of their Australian-born non-Indigenous and Indigenous counterparts. Methods A population-based linked data study, involving 767,623 singleton births in Western Australia between 1980 and 2010 was undertaken. Neonatal outcomes included preterm birth, post term births, intra-uterine growth restriction (assessed using the proportion of optimal birth weight) and low Apgar scores. These were compared amongst foreign-born women from low, lower-middle, upper middle and high income countries and Australian-born non-Indigenous and Indigenous women over two different time periods using multinomial logistic regression adjusted for covariates. Results Compared with Australian born non-Indigenous women, foreign-born women from low income countries were at some increased risk of extreme preterm (aRRR 1.59, 95% CI 0.87, 2.89) and very early preterm (aRRR 1.63, 95% CI 0.92, 2.89) births during the period from 1980 to 1996. During the period from 1997 to 2010 they were also at some risk of extreme preterm (aRRR 1.42, 95% CI 0.98, 2.04) very early preterm (aRRR 1.34, 95% CI 1.11, 1.62) and post term birth (aRRR 1.93, 95% CI 0.99, 3.78). During this second time period, other adverse outcomes for children of foreign-born women from low income and middle income countries included increases in severe (aRRR 1.69, 95% CI 1.30, 2.20; aRRR 1.72, 95% CI 1.53, 1.93), moderate (aRRR 1.54, 95% CI 1.32, 1.81; aRRR 1.59, 95% CI 1.48, 1.70) and mild (aRRR 1.28, 95% CI 1.14, 1.43; aRRR 1.31, 95% CI 1.25, 1.38) IUGR compared to children of Australian-born non-Indigenous mothers. Uniformly higher risks of adverse outcomes were also demonstrated for infants of Indigenous mothers. Conclusions Our findings illustrate the vulnerabilities of children born to foreign women from low and middle-income countries. The need for exploratory research examining mechanisms contributing to poorer birth outcomes following resettlement in a developed nation is highlighted. There is also a need to develop targeted interventions to improve outcomes for these women and their families.